Development of a forehand smash stroke model in table tennis for elementary school students - Muhamad Apriyawan Salilama; Sarjan Mile; Suriyadi Datau (Gorontalo State University, 2026)
Introduction: This research is driven by a identified research gap, specifically the low level of understanding and technical mastery among elementary school students regarding the forehand smash in table tennis. The urgency lies in providing a systematic and engaging alternative for Physical Education teachers to improve students' basic skills. This study aims to develop and evaluate the effectiveness of a forehand smash learning model at SD Negeri 07 Talaga Jaya. Methods: Using the Research and Development (RD) approach with the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation), data were collected through observations, interviews, and validation questionnaires from material and pedagogical experts. Results: The findings revealed that the developed model, featuring a visual instructional guidebook, was declared